Altered Long Noncoding RNA Expression Profile in Multiple Myeloma Patients with Bisphosphonate-Induced Osteonecrosis of the Jaw. (3rd July 2020) - Allegra, Alessandro; Mania, Manuela; D'Ascola, Angela; Oteri, Giacomo; Siniscalchi, Enrico Nastro; Avenoso, Angela; Innao, Vanessa; Scuruchi, Michele; Allegra, Andrea Gaetano; Musolino, Caterina; Campo, Salvatore
Abstract : Bisphosphonates (BPs) are inhibitors of osteoclast-mediated bone resorption used for the treatment of multiple myeloma (MM) patients with osteolytic lesions. Bisphosphonate-induced osteonecrosis of the jaw (BONJ) is an infrequent drug-caused adverse event of these agents. Long noncoding RNAs (lncRNAs) are a set of more than 200 base pairs, noncoding RNA molecules, which are critical posttranscriptional regulators of gene expression. Our study was aimed at evaluating 17 lncRNAs, whose targets were previously validated as key elements in MM, bone metabolism, and angiogenesis in MM subjects without BONJ (MM group), in MM subjects with BONJ (BONJ group), and a group of healthy controls (CTRL group). Our results demonstrated a different lncRNA profile in BONJ patients compared to MM patients and controls. Two lncRNAs (DANCR and MALAT1) were both downregulated compared to controls and MM, twelve (HOTAIR, MEG3, TP73-AS1, HOTTIP, HIF1A-AS2, MANTIS, CTD-2201E18, CTD1-2003C8, R-471B22, RP1-43E13, RP11-553L6.5, and RP1-286D6) were overexpressed in MM with BONJ, and one (H19) was upregulated compared with only MM. Two lncRNAs (JHDMD1 and MTMR9LP) had higher expression, but these differences were not statistically significant. The examined lncRNAs target several genes and metabolic pathways. An altered lncRNA signature could contribute to the onset of BONJ or have a protective action. Targeting these lncRNAs could offer a possibility for the prevention or therapy of BONJ.